Խոնարհման համակարգի տեղաշարժերը Գրիգոր Խլաթեցու «Բնագրական նշմարներ»-ում - Ծատուրյան, Տաճատ Տ․ վարդապետ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Глагол — одна из частей речи, пережившей несравнимо большие изменения в «Текстуальных проблесках» Григора Хлатеци. Живя и творя в послеклассический период и излагая мысли на среднеармянский языке, Хлатеци, тем не менее, в значительной степени был связан с классическим грабарором (девне- армянский язык). Вместе с этим, однако, есть много общностей и с ашхарабаром (новоармянский язык), связанных с формированием личных и безличных глаголов в системе спряжения и способов изменения наклонений глаголов при сравнении с грабаром. The verb is one of the parts of the speech that has undergone countless changes in “Original Notes” by Grigor of Khlat. Living and writing in the post-classical period, Grigor of Khlat, however, was largely associated with the Classical Armenian language while writing in the Middle Armenian. Nevertheless, there are many similarities with the Modern Armenian language as well, which are related to the formation of personal and impersonal verb forms in the conjugation system and the change of verb moods in comparison with the Classical Armenian language.
Keywords: Պատմություն; Բանասիրություն